Characterization of Plastic Materials used in the Automotive Industry (Impact- Stress) - A. Rojo; N. J. Ramirez; J. E. Salgado (The Minerals, Metals and Materials Society, 2011)
"This work aims to characterize the plastics used in a handgrip located in the car interior body in order to improve its design process and be able to predict its behavior when the part is subjected to impact test involving human casualties.Through stress analyses at high speeds and a video camera set up (front and side view), the reduction of area of specimen was obtained from image analysis, allowing to get the stress-strain real curve of the material.Continuing the characterization process a set of impact test was developed, where standard lzod configurations were used in unnotched specimens. From these tests were gotten displacement curves and absorption energy estimations.The proposed testing procedure allowed the acquisition of force and displacement data through time at various strain rates which are indispensable for the characterization of dynamic events. Using a specimen with a special configuration has shown a more detailed dynamic behavior resulting into more accurate numerical analyses within the design process.IntroductionIn the design process, one of the many analyses which take place is the impact test of the designed part. Nowadays there are many software capable to do these kind of analysis and each industry use the one they think it is convenient for them, but also the selected software has mathematic models that help to find the solution and the simulation of the case of analysis. These are not the only considerations that a company has to take into account, other one is the type of information and data necessary to feed the software. For this study we are going to focus on the acquisition of these data.The mail reason of this work is that generally the supplier gives the card of the material with all the characteristics and information requested by the buyer, but all of that information is acquired by standard methods, but it is inconvenient when the materials are polymers."